Strategic Agility and its Impact on Enhancing Competitive Advantage: A Field Study on Al Yaqeen Bank, Tripoli (Al-Farooq Journal of Sciences, 2026)
This research aimed to identify the impact of strategic agility, with its dimensions of customer agility (strategic sensitivity), partner agility (resource liquidity), and operational agility (leadership unity and collective commitment), on enhancing competitive advantage in its five dimensions (service costs, banking service differentiation, market share and focus, creativity and innovation, and social responsibility) at Al Yaqeen Bank, from the perspective of employees with varying characteristics such as gender, age, educational qualifications, years of experience, and job title. To achieve these objectives, the research adopted a descriptive methodology. The research population consisted of all 377 employees of Al Yaqeen Bank. A questionnaire was designed as the data collection tool and distributed using stratified random sampling to a sample of 133 employees from Al Yaqeen Bank branches in Tripoli. 121 responses were received, representing a response rate of 90.97%. The Statistical Package for the Social Sciences (SPSS) was used. The research yielded several key findings, the most important of which is:1. Al Yaqeen Bank demonstrates a high level of implementation of strategic agility measures. Strategic agility has three dimensions: customer agility, operational agility, and partner agility.2. Al Yaqeen Bank is characterized by a high level of competitiveness, demonstrated by its market share, focus, the excellence of its banking services, creativity and innovation, social responsibility, and the achievement of appropriate service costs.3. There is a statistically significant effect of overall strategic agility on enhancing Al Yaqeen Bank's overall competitive advantage.4. No significant differences were found in respondents' answers regarding the independent variable (strategic agility and its dimensions) and the dependent variable (competitive advantage and its five dimensions) based on demographic variables (gender, educational qualification, age, job title, and the interaction of these variables). However, differences were found based on years of service, favoring those with 5 to 10 years of service, who were more aware of the importance of strategic agility at the bank. Those with more than 10 years of experience were also more likely to assess the importance of competitive advantage.
Keywords: Strategic agility, competitive advantage, Commercial banks, Al Yaqeen Bank, operational agility, customer agility, service costs, market share, focus, creativity and innovation, social responsibility